CRISPR/Cas9-mediated development of Penicillium roqueforti strains deficient in roquefortine C and mycophenolic acid enables toxin-free blue cheese production - Chavez-Rosales, R; Gil-Duran, C; Rodriguez-Estevez, D (Elsevier B.V., 2026)
Penicillium roqueforti , a key fungus in the manufacture of blue-veined cheeses, can produce mycotoxins such as roquefortine C and mycophenolic acid. The production of these metabolites is highly strain- and condition-dependent. In industrial manufacture, hypotoxigenic P. roqueforti strains are typically used as controlled adjunct starters under standardized conditions, resulting in minimal mycotoxin accumulation, whereas naturally matured or artisan cheeses display more variable strain composition and ripening environments, which can elevate risk. In this context, the development of strains incapable of mycotoxin biosynthesis represents an important step toward safer cheese products. Here, we report the generation of P. roqueforti strains lacking the ability to synthesize roquefortine C and mycophenolic acid using CRISPR/Cas9. Single and double mutants deficient in one or both mycotoxins were obtained. Laboratory-scale cheeses produced under artisan-like conditions with these engineered strains contained no detectable levels of the target mycotoxins, in contrast to cheeses made with the wild-type strain. All mutants retained the ability to colonize cheese but displayed altered fungal biomass production compared to the native strain. These differences were consistent in curd and laboratory media and were not associated with changes in lipolytic or proteolytic activities. Further analyses revealed that while the absence of mycophenolic acid did not affect NaCl sensitivity, the lack of roquefortine C increased sensitivity to salt. Collectively, these results demonstrate the feasibility of producing mycotoxin-free blue cheeses using strains deficient in roquefortine C and mycophenolic acid biosynthesis, thereby laying the foundation for developing mycotoxin-free cheeses with engineered atoxigenic P. roqueforti strains. © 2025 Elsevier B.V.